The role of Hippo pathway in Zebrafish (Danio rerio) caudal fin regeneration - Brito, Gonçalo Miguel, 1988- (2011)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2011